Brief Report: Association Between Menopause and Unprotected Sex in High-Risk HIV-Positive Women in Mombasa, Kenya. (15th April 2017) - Goyette, Marielle S.; Wilson, Kate S.; Deya, Ruth; Masese, Linnet N.; Shafi, Juma; Richardson, Barbra A.; Mandaliya, Kishorchandra; Jaoko, Walter; McClelland, R. Scott
Abstract : Objective: Many HIV-positive women now live well beyond menopause. Postmenopausal women are no longer at risk for pregnancy, and some studies suggest that they may use condoms less often than premenopausal women. This study tests the hypothesis that, in HIV-positive women who report trading sex for cash or in-kind payment, unprotected sex is more common at postmenopausal visits compared with premenopausal visits. Design: Prospective cohort study of HIV-positive women ≥16 years old in Mombasa, Kenya. Methods: At enrollment and monthly follow-up visits, participants completed a standardized interview. Study clinicians collected genital samples at enrollment and quarterly visits. Menopausal status was assessed annually. The primary outcome of unprotected sex was determined by detection of prostate specific antigen (PSA) in vaginal secretions. Results: This study followed 404 HIV-positive women who contributed 2753 quarterly examination visits. Detection of PSA was less frequent at postmenopausal visits compared with premenopausal visits [55/554, 10.5% versus 394/2199, 17.9%; relative risk (RR) 0.58, 95% confidence interval (CI): 0.39 to 0.87]. Adjusting for age diminished the association between menopause and PSA detection (adjusted RR 0.73, 95% CI: 0.47 to 1.14). At visits where women reported sexual activity in the past week, they reported similar rates of 100% condom use at postmenopausal and premenopausal visits (RR 0.99, 95% CI: 0.87 to 1.13). Conclusions: In this population of high-risk HIV-positive Kenyan women, postmenopausal status was not associated with a greater risk of unprotected sex. The relationship between menopause and unprotected sex is likely context specific and may differ with varying risk groups, regions, and levels of exposure to sexual health education.